Un nouveau cas de sépultures multiples à Troyes, Place de la Libération (Aube, Moyen Âge) - Cécile Paresys; Dominique Castex; Cédric Roms; Isabelle Richard; Stéphanie Degobertière (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The excavations carried out before the construction of an underground car park in the center of Troyes enabled a thorough study of six burial pits containing over a hundred individuals. That they are the result of abrupt mortality events is demonstrated by the simultaneous deposit of the bodies, sometimes in several layers. Archives indicate that these graves are in that part of the parish cemetery which was allocated to the town’s infirmary. In the particular context of acute mortality events, the use of archaeo-anthropological methods (analysis of corpse deposition and of age and sex distribution at death) can provide new elements for consideration. The synthesising of the data concerning the simultaneous burials at Troyes with those related to another osteological series linked to abrupt mortality events (plague epidemic) demonstrates the variability of the situations in events of this type, as much in funerary practice as in the demographic impact of the events as revealed by the mortality profile of the archaeological samples.